2018
DOI: 10.1088/1361-6455/aacb45
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state characteristics of helium–alkali tetramers

Abstract: Li, 23 Na, 39,40,41 K, 85,87 Rb or 133 Cs, were studied using diffusion Monte Carlo method. Besides ground-state energies, exact distribution functions were evaluated. Spatial arrangements of atoms in clusters qualify He-A tetramers as transitional systems, which reveal halo-like spatial extension. On the one hand, swapping 4 He by 3 He atom in a He-Li tetramer, one can trace how quasi-halo structure transforms into halo structure. On the other hand, swapping 3 He by 4 He in He-A tetramer reveals behavior pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Constituents and tetramer types are distinguished with different symbols (see the legends). Available published data were taken from helium 20 , helium-alkali 21 , and helium-tritium tetramers 31 . Necessary additional features, like the structure properties 〈 r 2 〉, and new data for all other clusters included in the Figure were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Constituents and tetramer types are distinguished with different symbols (see the legends). Available published data were taken from helium 20 , helium-alkali 21 , and helium-tritium tetramers 31 . Necessary additional features, like the structure properties 〈 r 2 〉, and new data for all other clusters included in the Figure were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, when a system is partially constrained by asymmetrical potential barriers, a mixed system can exhibit also small deviations below the universal line. For instance, an alkali atom in He-alkali tetramers 21 prevents symmetric configurations: the helium atoms group together in one side of the alkali atom instead of surrounding it, limiting the size of the cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A thorough analysis for a large set of pure and mixed weakly-bound atomic dimers, trimers, and tetramers showed that universal size-energy scaling extends even below the halo area 21 , in the so called quasi-halo region. Four-body systems with large size were found in Helium and Helium-alkali tetramers 27 , 28 , but also in pentamers 29 . It is therefore interesting to explore the existence of a universal relation between energy and size of five-body clusters, in a wide range extending from weakly-bound quantum halo systems to classical ones.…”
Section: Introductionmentioning
confidence: 99%